2019
DOI: 10.1002/jccs.201800368
|View full text |Cite
|
Sign up to set email alerts
|

Pyrite oxidation mechanism in aqueous medium

Abstract: The mineral pyrite is considered the most common form of the sulfide minerals. Its oxidation is a very important process in nature, which involves in the redox recycling of iron. However, because of the growing need for the industrial production, sulfide oxidation produces more and more acid mine (or rock) drainage. This acid drainage has become a heavy economic and environmental problem. This review describes the oxidation mechanism of pyrite in an aqueous medium, including general oxidation and microbial oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 104 publications
(152 reference statements)
1
11
0
Order By: Relevance
“…In this room, no archeological wood is stored. Figure 2 Such archeological objects are considered to be the main source of pollution by H 2 S. Indeed, pyrite oxidizes naturally following the reaction [23][24][25][26]:…”
Section: Description Of Areas Under Monitoringmentioning
confidence: 99%
“…In this room, no archeological wood is stored. Figure 2 Such archeological objects are considered to be the main source of pollution by H 2 S. Indeed, pyrite oxidizes naturally following the reaction [23][24][25][26]:…”
Section: Description Of Areas Under Monitoringmentioning
confidence: 99%
“…In the absence of Cu 2+ in the acid solution, Fe 3+ and O 2 are the main contributors to oxidation of pyrite, according to previous research reports. 5,37 Moreover, it has been reported that Fe 2+ , Fe 3+ , S 2− , S 0 , and SO 4 2− are present in acid solution with the progress of pyrite oxidation. 1,8,31,38 Based on the reports of Zhu et al 60 and Feng et al, 37…”
Section: X-ray Photoelectron Spectroscopy (Xps) Measurementsmentioning
confidence: 99%
“…5,37 Moreover, it has been reported that Fe 2+ , Fe 3+ , S 2− , S 0 , and SO 4 2− are present in acid solution with the progress of pyrite oxidation. 1,8,31,38 Based on the reports of Zhu et al 60 and Feng et al, 37…”
Section: X-ray Photoelectron Spectroscopy (Xps) Measurementsmentioning
confidence: 99%
“…The second proposed mechanism is simpler for description and involves only two steps. According to the first step, colloidal sulfur species are generated via a reaction presented with Equation ( 10) that is similar to the processes described with the Equations 11-13 in Feng et al [26] The second step of this mechanism resembles a direct reaction between the copper from the brass surface and the colloidal sulfur species thus generating chalcocite phase Cu 2-x S, as presented with Equation (11). The possibility for the occurrence of the second step reaction can be supported by the fact that colloidal sulfur species dispersed in an aqueous solution are more hydrophilic and consist of S 6 and S 7 molecules and are thus more reactive than the most abundant allotropic modification of sulfur, that is, cyclooctasulfur that consists of S 8 ring molecules.…”
Section: Possible Mechanismmentioning
confidence: 99%